Construction and Analysis of a Model of Group Receipt of IoT Elastic Data in a Wireless Access Node - Stepanov, S. N.; Korotkova, V. I.; Kanischeva, M. G.; Pshenichnikov, A. P. (Systems of Signals Generating and Processing in the Field of on Board Communications (Online), 2023)
A mathematical model of the process of servicing by isolated cell of LTE standard a stream of sessions for elastic data transmission has been constructed and investigated. The model assumes that the sources of sessions including telemetry devices and video cameras with recording set by the system surveillance operator, which provides resources for transmitting the collected data to surveillance centers. The analyzed model takes into account that the data is transferred has elasticity, i.e. file transfer rates may vary within certain limits without service quality loss. This possibility is used in current and prospective wireless communication systems to increase the occupancy rate of the information transmission resource. The model also takes into account the impulsive nature of the process of receiving requests for data transmission. For this purpose, it is assumed that requests arrive in groups of random size. If the transfer rate of files under maintenance cannot be reduced, then the request received at that moment is rejected and is put on hold. It is assumed that the transmitted information is subject to aging. If the request has not been served within a certain time, the request is lost without renewal. Using the model, definitions are given for the main indicators of servicing requests, an algorithm for their evaluation is developed, and numerical examples are given that illustrate the use of the model to analyze the properties of elastic data transmission and estimate the required amount of resource to service incoming requests with a given quality.